A product arrangement optimization method to reduce packaging environmental impacts. Issue 1 (March 2020) - Truong, C.T.T.; Amodeo, L.; Yalaoui, F.; Hautefaye, J.C.; Birebent, S.
Abstract: The Three-dimensional Open Dimension Rectangular Packing Problem (3D-ODRPP) is one of the most important optimization problems arise in reducing waste and shipping cost of packing and shipping industries. The 3D-ODRPP aims at seeking the length, width and height of a rectangular box of minimal volume that can pack a given rectangular products. Most 3D-ODRPP models in the literature use too many extra binary variables and don't consider the equilibrium of product placement. This study presents an improved mathematical model for the 3D-ODRPP. The proposed model uses fewer decision variables and constraints to define product orientation. It also adopts the full base support (FBS) constraint as a product supporting condition to guarantee packaging stability and avoid infeasible arrangements. Literature instance tests show the improvement in packaging stability of the proposed method compared with existing methods. Industrial benchmark demonstrates that, by solving the 3D-ODRPP, the proposed method can reduce package volume and create economic and ecologic gains.